Autism, bullying, and mental health: a comprehensive systematic review - Daghustani, Wid H.; Abo Hamza, Eid G.; Hogg, Rachel; Moustafa, Ahmed (Frontiers in Psychiatry, 2025)
This review investigates the relationship between autism, vulnerability to bullying, and the impact of bullying on mental health for this cohort. Neurotypical social mores can be exclusionary, creating social risks for autistic people, while differences in communication and social engagement can impact peer-to-peer interaction, making autistic people more vulnerable to bullying and social discrimination. The current systematic review investigates risk factors related to the bullying of autistic people, considering both societal and individual factors. Our PRIMA guided search reported 74 studies. Our results show that the prevalence of bullying of autistic individuals vary across studies, autistic individuals face verbal, social, and physical bullying, and that bullying was found to lead to the development of depression, anxiety, and social withdrawal. The importance of education, creating inclusive environments, building resilience, collaborative efforts, policy and legislation, mental health support, and prevention and protection implications, are discussed. By implementing these strategies, we can work to reduce vulnerability to bullying in autistic people as well as promote their overall well-being. This review emphasises the importance of comprehensive interventions and support systems in combating bullying and improving the lives of autistic people.